Bioprospecting nutraceuticals from soybean (Glycine max) seed coats and cotyledons - KUMAR, ASHUTOSH; V, RAMESH K; SINGH, CHANDU; V, SRIPATHY K; AGARWAL, DINESH K; PAL, GOVIND; KUCHLAN, MRINAL K; SINGH, RAJIV K; PRABHA, RATNA; KUMAR, S P JEEVAN (The Indian Journal of Agricultural Sciences, 2019)
Food security coupled with nutritional security is a great concern to address the menace of malnutrition. In the present study, total phenolic contents and antioxidant potential of 35 soybean genotypes have been determined (2018). Besides, the solvent system for efficient extraction of total phenolic content coupled with antioxidants (nutraceuticals) has been optimized. The results revealed that the higher total phenolic contents from soybean seed coats and cotyledons were obtained in acetone-water-acetic acid (70:28:02, v/v) mixture. Total phenolic content (TPC) in soybean genotypes were in the range of 2.58–51.37 μg/mL and 4.26–12.76 mg/mL in seed coats and cotyledons, respectively. In soybean seed coats, higher phenolic content was observed in JS76-205 genotype with 128.5 μg/ml, while JS-2 and MAUS-158 showed 9.00 μg/mL. On the other hand, TPC derived from soybean cotyledons of NRC-37 and MAU-81 showed 12.76 mg/mL; whereas in PS-1347 resulted 4.26 mg/mL. Characterization of phenolic compounds in soybean seed coat and cotyledon revealed the presence of protocatechuic acid, p-hydroxy benzoic acid, 4-hydroxy benzaldehyde, vanillic acid, vanillin, p-coumaric acid and ferulic acid. Further, antioxidant studies performed from soybean seed coats and cotyledons were in the range of 9.00–128.50 μg eq. ascorbic acid and 2.13–4.27 mg eq. ascorbic acid, respectively. This study demonstrates that the TPC derived from soybean coat and cotyledon can be used not only as nutraceutical but also ensure food and nutritional security.